Microgrid Technologies for Remote Islands of Bangladesh - A Review - Dodaev, Zohar Al; Aziz, Tareq; Ali, Md. Sumon; Ibrahim, Saleh (Control Systems and Optimization Letters, 2024)
Issues about fuel exhaustion, electrical shortages, and global warming are growing increasingly serious as a result of the global energy crisis. Solar and wind energy, both of which are clean and sustainable, provide solutions to these issues via distributed generators. Microgrids have emerged as a research hotspot as a crucial interface for connecting the power produced by dispersed renewable energy generators to the electrical system. The main objective of this paper is to review the technical aspect of microgrid in remote islands of Bangladesh. Microgrid technologies provide great promise for tackling the particular energy difficulties encountered by Bangladesh's outlying islands. This review explained the application, benefits, and limitations of microgrid solutions in the context of these isolated places in depth. The review draws on a wide range of academic literature and addresses the technical aspects of microgrid architecture and renewable energy source integration. The evaluation looks at how renewable energy sources like hydroelectric systems, wind turbines, and solar photovoltaics (PV) can be integrated. To identify the best combination for producing power, this entails evaluating the resource availability, intermittency, and variability of various renewable sources. Furthermore, the unmet load, electricity in excess and technological future of technical aspect has been discussed in this review. Employment in society, comfortable life and ecosystem of social aspect of microgrid has also been discussed. Risk analysis, sensitivity analysis and scenario analysis have been explained here in this paper. This review provides significant insights for policymakers, academics, and practitioners aiming to deploy efficient and sustainable energy solutions for Bangladesh's remote islands. This review will also assist decision-makers in adopting microgrids for rural electrification and in establishing regulations that are helpful and clear for the operation and integration of microgrids. System effectiveness, energy storage, and grid management breakthroughs may result from research and development of microgrid technology.